1999
DOI: 10.1111/j.1471-0307.1999.tb02855.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein concentration on the properties and structure of concentrated yogurts

Abstract: Reading RG6 6AP, UK Concentrated yogurts were produced by traditional (control), direct reconstitution, ultrajiltration and reverse osmosis techniques. The membrane techniques were applied either before or soon after incubation. The physical properties of the samples were monitored using a penetrometer (set yogurt) and viscometer (stirred yogurt), and the results indicated that different manufacturing techniques led to differences in the rheology of the concentrated yogurts. As expected, samples with high prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…The rheological properties of set-style, that of stirred gels and the whey retention capacity were correlated with each other in agreement with the literature (Cayot et al, 2003;Lee and Lucey, 2006;Lucey et al, 1997aLucey et al, , 1998aOzer et al, 1999). They all appeared to be greatly influenced by the pH value on stirring.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The rheological properties of set-style, that of stirred gels and the whey retention capacity were correlated with each other in agreement with the literature (Cayot et al, 2003;Lee and Lucey, 2006;Lucey et al, 1997aLucey et al, , 1998aOzer et al, 1999). They all appeared to be greatly influenced by the pH value on stirring.…”
Section: Discussionsupporting
confidence: 83%
“…The factors responsible for the increase in viscosity of stirred yoghurts are therefore essentially the same as those that increase the firmness of set-style yoghurts. A few recent studies have shown direct correlations between rheological properties or spatial properties of set-style and stirred yoghurts (Cayot et al, 2003;Lee and Lucey, 2006;Ozer et al, 1999;Van Marle, 1998;Van Marle and Zoon, 1995). However, as far as we know, the effect of the structural properties of set-style gels on the structure recovery of stirred yoghurt has not been yet investigated.…”
Section: Introductionmentioning
confidence: 95%
“…(1989) that UF offers an excellent alternative to the cloth bag method for labneh making. Moreover, it has been indicated by Ozer et al . (1999a,b) that different manufacturing techniques led to differences in the rheology of concentrated yogurts and that rheological behaviour of labneh depended on the protein concentration and the severity of mechanical agitation during membrane treatment.…”
Section: Miscellaneous Propertiesmentioning
confidence: 73%
“…This may be due to the incorporation of MPC and the draining of whey enhancing the casein concentration and ultimately strength of casein network due to greater non-covalent interactions. Furthermore, the cloth bag draining has apparently allowed enough time for establishment of a strong gel matrix (Ozer et al 1999). Removal of whey is far more important than the casein content to achieve the required viscoelastic behaviour (Bong & Moraru, 2014).…”
Section: Resultsmentioning
confidence: 99%